(untitled) (The Journal of Medicine, Humanity and Media, 2026)
This article systematically reviews the Culture-Centered Approach (CCA), a theoretical framework pioneered by Mohan J. Dutta, a distinguished professor in the Department of Communication at Massey University, New Zealand. Against the backdrop of growing global health inequities, mainstream health communication models have been widely criticized for their individualistic assumptions and top-down intervention logic. Grounded in postcolonial critique and Marxist political economy, and informed by Dutta’s transnational life and academic trajectory, CCA constructs an analytical framework centered on the dynamic interplay of structure, culture, and agency. This study traces the theoretical origins of CCA, critically examines the limitations of dominant health communication paradigms, and elucidates how CCA reconceptualizes culture as a fluid field of meaning-making. It argues that health communication practices should be co-created through dialogue within communities, thereby empowering marginalized groups. As a profound challenge to mainstream models, CCA offers significant theoretical and practical insights for health communication research and intervention in Global South contexts, including China—particularly in studying rural populations, migrants, and other marginalized communities.